2000
DOI: 10.1111/j.0435-3684.2000.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in social and spatial marginality

Abstract: The purpose of this paper is to present a conceptual taxonomy of marginality resulting from two counterposed structural conditions within laissez-faire on the one hand and controlled markets on the other. Marginality is a complex condition of disadvantage that individuals and communities may experience because of vulnerabilities which may arise from unequal or inequitable environmental, ethnic, cultural, social, political and economic factors. A typology of marginality is based on two primary and two derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 54 publications
1
21
0
2
Order By: Relevance
“…The concept is closely related to ideas of marginality which is a condition of disadvantage that may arise from unfavourable environmental, cultural, social, economic and political factors. Mehretu et al (2000) in their review of the concept of marginality noted that the literature on uneven development treats the phenomenon of marginality as a generic concept of socio-economic disadvantage in which inequality and inequity are treated as synonymous. Arguably, similar perspectives can be traced in the literature on peripherality (Hall2007).…”
Section: Peripheralityas Marginalitymentioning
confidence: 99%
“…The concept is closely related to ideas of marginality which is a condition of disadvantage that may arise from unfavourable environmental, cultural, social, economic and political factors. Mehretu et al (2000) in their review of the concept of marginality noted that the literature on uneven development treats the phenomenon of marginality as a generic concept of socio-economic disadvantage in which inequality and inequity are treated as synonymous. Arguably, similar perspectives can be traced in the literature on peripherality (Hall2007).…”
Section: Peripheralityas Marginalitymentioning
confidence: 99%
“…En fait, on pourrait dire qu'il n'y a pas une ségrégation économique mais bien des ségrégations économiques. Ces dernières dépendent de processus différents et opèrent à des échelles diverses (Mehretu et al 2000 ;Pigozzi 2004). Elles agissent les unes sur les autres, conférant à la ségrégation économique un caractère particulièrement complexe.…”
Section: Qu'est-ce Que La Ségrégation éConomique ?unclassified
“…A series of studies in the USA have shown the importance of racial and class tensions in shaping urban form. This has been particularly evident in the Detroit region, which, as argued by Lawrence Sommers, Assefa Mehretu, and Bruce Pigozzi, consists of some of the richest and poorest districts in the nation (Mehretu et al, 2000;Pigozzi, 2004;Sommers et al, 1998;). In addition, work by Joe Darden, Richard Hill, June Thomas and Richard Thomas has shown that it has not only been class conflicts but also racial tensions that have been critical in decentralizing greater Detroit (Darden et al, 1987;Darden and Kamel, 2000).…”
Section: Resultsmentioning
confidence: 99%